2020
DOI: 10.1016/j.ancene.2020.100270
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air quality of a less industrialized region of India (Kerala) during the COVID-19 lockdown

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Chandigarh showed a decrement of 16.3% from 21-days before lockdown to the first phase of lockdown and then showed an enhancement of 5.4% in the second phase of lockdown compared to the first phase. A sharp reduction in the range of 24-67% is also reported over Kerala amid lockdown and meteorological changes [39].…”
Section: Carbon Monoxide (Co)mentioning
confidence: 84%
See 2 more Smart Citations
“…Chandigarh showed a decrement of 16.3% from 21-days before lockdown to the first phase of lockdown and then showed an enhancement of 5.4% in the second phase of lockdown compared to the first phase. A sharp reduction in the range of 24-67% is also reported over Kerala amid lockdown and meteorological changes [39].…”
Section: Carbon Monoxide (Co)mentioning
confidence: 84%
“…PM measurements over Gadanki, a rural site in south India revealed that PM2.5 and PM10 dropped down by $47% and 50% respectively from pre-lockdown (15th Feb -21st Mar 2020) to lockdown [36]. Similarly, studies over south India reported that PM2.5 reduced by 53%, 15-22%, and 24-47% over Kunnur, Bengaluru and Kerala respectively during lockdown over pre-lockdown (1st Jan-22nd Mar 2020) [30,39,40]. Thus, a decrease in traffic density, human mobility, shutting of industries drastically reduced PM pollution over India leading to the emergence of blue sky after a decade [25,43].…”
Section: Particulate Matter (Pm)mentioning
confidence: 98%
See 1 more Smart Citation
“…The efficiency of such cyclones ranges between 75 and 85 %, for particles larger than 20 μm in size. However, this is not sufficient in terms of the objectives laid down in the EU Directive 2008/50/EC on ambient air quality and cleaner air for Europe [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 97%
“…In China, the country where SARS-CoV-2 had its origin and where the isolation measures were started in January 2020, the reduction of atmospheric pollutants, such as NO 2 (Venter et al 2020 ; Wang et al 2020 ; Chen et al 2020 ; Chen et al 2021 ) and PM 2,5 (Venter et al 2020 ; Chen et al 2020 ; Giani et al 2020 ; Shi et al 2021 ), has been verified after the adoption of measures to cope Covid-19. In Southeast Asia, air quality during the pandemic period was also object of study, with improvement in cities like India (Mahato et al 2020 ; Thomas et al 2020 ; Tyagi et al 2021 ). In Pakistan, on the other hand there were no significant changes in PM 2,5 (Mehmood et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%